RETROSPECTIVE MULTICENTRIC STUDY ON THE POST-SURGERY SYMPTOMATIC AND OBJECTIVE IMPROVEMENT OF BENIGN PROSTATIC HYPERPLASIA PATIENTS - GUPTA, NEERAJ; MAINI, SUNIL KUMAR; PAL, VISHNU; TIWARI, PUNIT; BM, LOYA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: To evaluate patients of benign prostatic hyperplasia (BPH) preoperatively and identify those who would benefit from surgery, to evaluate outcome of surgery for BPH with respect to symptomatic and objective improvement of patients, and to compare the results of different surgeries for BPH being done different hospitals at Bhopal, which included transurethral resection of the prostate (TURP), transurethral incision of prostate (TUIP)/bladder neck incision (BNI), and Freyer’s prostatectomy? Methods: The present study was carried out at different hospitals of Bhopal. Patients presenting to the surgery outpatient department with symptoms of obstruction, namely, weak urinary stream, frequency hesitancy, intermittency, urgency, nocturia, etc., were included in the study. Some of the subjects included were patients presenting during emergency timings with complaints of retention of urine or occasionally other symptoms. The American Urological Association (AUA) Symptom Index questionnaire was administered to all such patients. They were also evaluated by ultrasound examination and patients having BPH on ultrasound (USG) were further evaluated by uroflowmetry. Results: Prostatic weight correlated well with the maximum urinary flow rates with an inverse relationship. Both maximum and average urinary flow rates (Q max and Qav) were improved by all the three surgeries However, TURP and Freyer’s prostatectomy showed greater improvement as compared to TUIP/BNI. Combination of AUA scoring, USG, and uroflowmetry helped us document improvement in our BPH patients and compared it favorably with other studies. Conclusion: Uroflowmetry was a simple assessment tool easy to learn and use. It was also inexpensive and formed a useful extension to clinical examination providing objective evidence of obstruction. It also helped to indirectly quantity the severity of obstruction. Symptom severity did not correlate with prostate size. Small prostates caused symptoms in the severe range also while even large prostates sometimes caused little symptoms. Prostatic weight correlated well with the maximum urinary flow rates with an inverse relationship.